Effectiveness of Revenue Budget Implementation and Regional Shopping in Lumajang Regency - Wena Kusharyanti; Ika Devy Pramudiana; Eny Haryati (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to describe and analyze: the effectiveness of the implementation of the Revenue and Expenditure Budget policy and the implications of the implementation of the Regional Budget and Expenditure policy in Lumajang Regency. The data analysis technique uses the technique developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that regional financial policies in Lumajang Regency, especially the policy of increasing Regional Original Revenue (PAD), are inseparable from the Central Government's policies in the framework of financial relations between the Central and Regional Governments. Meanwhile, the Lumajang Regency Government's policies to increase Regional Original Revenue (PAD/Pendapatan Asli Daerah) include: Digitalization to increase the efficiency and transparency of financial management, Adjustment of regional taxes and levies, Re-collection of taxpayers, Cooperation with the private sector and NGOs in the management and collection of regional taxes and Improvement of regional tax management management. The model of the implementation of the Regional Original Revenue (PAD) policy implementation model in Lumajang Regency is Top Down. The Government of Lumajang Regency, East Java is committed to continuing to encourage an increase in Regional Original Revenue (PAD). The contribution of Lumajang Regency's PAD in 2024 compared to the APBD (Anggaran Pendapatan Belanja Daeerah) structure only reaches 16 percent, so that to meet the needs of the expenditure budget in the APBD budgeting structure, it still depends on transfer funds, To reduce dependence on transfer funds, the government is optimizing regional tax revenues, especially from the Rural and Urban Land and Building Tax (PBB-P2). The implication is that to increase regional tax and levy revenues, efforts are needed to increase production and business capacity in the regions. Increasing production capacity and business activities is an important factor to increase regional tax and levy revenues. In addition, it is also necessary to increase the capacity of regional tax administration as one of the requirements to increase tax capacity and effort in the regions (taxable capacity and tax effort).